THE APPLICATION OF DERIVATIVE MISCONDUCT IN THE WORKPLACE: A CRITICAL ANALYSIS OF National Union of Metalworkers of South Africa obo Nganezi v Dunlop Mixing and Technical Services (Pty) Limited 2019 (5) SA 354 (CC) - Simphiwe P Phungula (Obiter, 2023)
In modern South African law, employees have several fundamental rights, the right to strike being one of those rights. This right is enshrined in the Constitution of the Republic of South Africa, 1996 (the Constitution) and also in the Labour Relations Act 66 of 1995 (the LRA); both statutes provide that every employee has the right to strike (s 64(1) of the LRA and s 23(2)(c) of the Constitution). However, for a strike to be protected as legal strike action, at least 48 hours’ notice of the commencement of the strike must be given, in writing, to the employer (s 64(1)(b) of the LRA). If employees misconduct themselves – for example, engage in acts of violence during a protected strike – the employer is entitled to dismiss those employees on the grounds of misconduct (Schedule 8, item 7 of the Code of Good Practice under the LRA). However, if the employer is unable to identify the responsible employees (the perpetrators), the question is whether the employer can request other employees to identify the perpetrators. If the answer to this is yes, the next question is whether the employer can dismiss these employees if the employees do not want to identify the “perpetrators”.To answer these questions, employers have relied on the principle of “derivative misconduct” to discipline employees during strike action where employees responsible for misconduct cannot be identified and other employees fail, when requested, to come forward and assist the employer to identify those responsible. Derivative misconduct is a principle that is neither defined nor appears in any labour legislation. It has been developed by the courts and used by employers as a concept to require an employee to come forward and give information about other employees who have misconducted themselves during protest action. Since derivative misconduct is not defined in labour legislation, a consideration of the judgments that have considered the scope and application of this principle on a particular set of facts demonstrates the difficulties of its application. Before the Constitutional Court judgment in NUMSA obo Khanyile Nganezi v Dunlop Mixing and Technical Services (Pty) Ltd (2019 (5) SA 354 (CC)), several judgments attempting to develop or clarify the concept either found derivative misconduct did not exist on the particular facts or just expressed obiter views on the issue. This led to varying decisions on the application of derivative misconduct. The Constitutional Court has now finally sought to articulate and grapple with this concept.